Inhibition of mevalonate metabolism by statins augments the immunoregulatory phenotype of vascular endothelial cells and inhibits the costimulation of CD4+ T cells. Issue 3 (8th November 2021) - Agur, Timna; Wedel, Johannes; Bose, Sayantan; Sahankumari, A. G. Pramoda; Goodman, Daniel; Kong, Sek Won; Ghosh, Chandra C.; Briscoe, David M.
Abstract : The statin family of therapeutics is widely used clinically as cholesterol lowering agents, and their effects to target intracellular mevalonate production is a key mechanism of action. In this study, we performed full transcriptomic RNA sequencing and qPCR to evaluate the effects of mevalonate on the immunoregulatory phenotype of endothelial cells (EC). We find that mevalonate‐dependent gene regulation includes a reduction in the expression of multiple pro‐inflammatory genes including TNFSF4 (OX40‐L) and TNFSF18 (GITR‐L) and a co‐incident induction of immunoregulatory genes including LGALS3 (Galectin‐3) and LGALS9 (Galectin‐9). In functional assays, pretreatment of EC with simvastatin to inhibit mevalonate metabolism resulted in a dose‐dependent reduction in the costimulation of CD45RO + CD4 + T cell proliferation as well as IL‐2, IFNγ and IL‐6 production versus vehicle‐treated EC. In contrast, pre‐treatment of EC with L‐mevalonate in combination with simvastatin reversed phenotypic and functional responses. Collectively, these results indicate that relative mevalonate metabolism by EC is critical to sustain EC‐dependent mechanisms of immunity. Our findings have broad relevance for the repurposing of statins as therapeutics to augment immunoregulation and/or to inhibit local tissue pro‐inflammatory cytokine production following transplantation. Abstract : Treatment of endothelial cells with statins is associated with reduced expression of pro‐inflammatory genes, induced expression of immunoregulatory genes and a dose‐dependent inhibition in the costimulation of CD4 + CD45RO + memory T cell proliferation and cytokine production.